Application of Ecoenzyme with Different Concentrations on the Growth of Mulyo Banana (Musa Paradisiaca L.) from In Vitro Culture Post Acclimatization - Faradilla; Nur Hidayat (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2025)
One of the factors that affects seedling growth during the post-acclimatization period is the adequacy of nutrients needed by the seedlings. Therefore, the right method is needed so that the seedlings can grow optimally. One of them is by meeting the nutrient needs with organic fertilization. The organic fertilizer used is ecoenzyme. Ecoenzyme is a product of the fermentation of organic kitchen waste such as fruit pulp, fruit peels, and vegetables by processing them through a fermentation process. Ecoenzyme has a characteristic brown color and a distinctive fermentation aroma, namely a strong sweet and sour. The purpose of this study was to determine the optimal concentration of ecoenzyme for the growth of Mulyo bananas from tissue culture. The study was conducted in the pilot garden of Plantation Crops Cultivation of the Samarinda State Agricultural Polytechnic, which was carried out for 3 (three) months from March to June 2024. The provision of Ecoenzyme with different concentrations consisted of 3 treatment levels, each treatment level was repeated 10 times, namely: M0: No treatment (control), M1: 20 ml Ecoenzyme / l and M2: 40 ml Ecoenzyme / l. To determine the optimal concentration, the data were calculated using a simple average. The results showed that the growth of height and number of leaves of Mulyo banana seedlings after acclimatization at the age of 30, 60 and 90 HST with a concentration of 20 ml ecoenzyme/l (M1) was the optimal concentration.